Co-Creation of Value dan Customer Experience: Aplikasi dalam Mobile Banking di Indonesia - jodjana, Sheny; Rahayu, Siti; Widjaja, Fitri Novika (STKIP Singkawang, 2024)
AbstractThis study aims to analyze the effects of co-creation of value on the customer experience in mobile banking usage in Indonesia, focusing on the roles of consumer creativity, connectivity, and knowledge. The study uses a quantitative approach with a survey method involving 210 respondents who are active users of mobile banking applications in Indonesia. The collected data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that co-creation of value has a positive impact on customer experience, with consumer creativity and connectivity being the main factors supporting value co-creation. Consumer knowledge shows no significant effect on the model. These findings suggest that consumer's involvement in the co-creation process strengthens the relationship between banks and customers, especially through digital platforms. This research's practical implication is that the banks should focus more on the creativity and connectivity aspects in developing mobile banking services to enhance customer experience and strengthen competitive positioning in the market.Keywords: Co-Creation of Value, Customer Experience, and Mobile Banking